Diachronic Morphological Study In Pontianak City As Waterfront City - Gultom, Bontor Jumaylinda Br; Andi, Andi; Jati, Dian Rahayu; Affrilyno, Affrilyno (Journal of Regional and City Planning, 2025)
This study presented a diachronic analysis of the morphological development of Pontianak City as a waterfront city. The diachronic time frame is based on several old maps, including those made in 1846, 1898, 1942, 1980, and 2020. The objective of this study was to determine the direction and patterns of waterfront city development in terms of road network patterns. Space syntax method was selected because this method analyzes urban morphology through a configuration model and produces spatial patterns in relation to the social character of the residents in the city. Integration analysis was performed to convey the tendency and probability of the next direction of development. The results showed that the direction of the development orientation of Pontianak City underwent some changes over periods, starting from river-oriented to land-oriented due to the construction of ditches and bridges. In fact, the development patterns of Pontianak City caused some urban problems, namely North Pontianak (Area C) became left behind and segregated from the city centre (Area A). Space syntax can predict the development of Pontianak City based on the socio-economic conditions of the community. However, political conditions and policies are unpredictable yet able to change the direction of the city’s development to be guided.